Assessing the determinants of out-of-pocket health expenditures among Cambodian households in informal employment using survey data - Andrea Hannah Kaiser; Sovathiro Mao; Jesper Sundewall; Marlaina Ross; Sokunthea Koy; Searivoth Vorn; Pichenda Koeut; Bjoern Ekman (International Journal for Equity in Health)
Abstract Background As the deadline for the Sustainable Development Goals approaches, financial protection in Cambodia remains inadequate, especially for nonpoor informal workers lacking formal social health protection coverage or access to other prepayment schemes. This exposes them to high out-of-pocket health expenditures (OOPE) and related financial hardship. To better understand the drivers behind these expenditures, our study aims to model their healthcare, health, and social determinants and to assess their relative importance. Methods In 2023, we conducted a cross-sectional multistage clustered sampling survey across seven Cambodian provinces, surveying 3,254 households engaged in informal employment and not covered by any formal social health protection scheme. The survey gathered information on households’ use of outpatient and inpatient care and associated OOPE. We employed generalized linear models (GLMs) to analyse the healthcare, health, and social determinants of OOPE and the OOPE budget share (the proportion of total annual household consumption expenditure spent on OOPE) and applied Shapley decomposition analysis to quantify the relative contributions of these determinants to the explained variance in our outcomes. Results Healthcare variables were the dominant contributors to the explained variance in all outcomes (41.36–50.73%), followed by health factors. While several social variables were significant, only the wealth quintile made notable contributions to explaining variance in our outcomes. The key healthcare contributors included the sector type and level of care, and the number of outpatient medications. Important health contributors included illness severity and the presence of chronic illnesses or noncommunicable diseases. Conclusions Our findings emphasize the necessity of integrating nonpoor informal workers and their dependents into formal prepayment schemes to reduce OOPE and enhance financial protection on Cambodia’s path toward universal health coverage. Strategically engaging with private providers and pharmacies to improve access to essential services and medicines, coupled with the implementation of an effective referral system are important policy considerations to this end. Further research is needed on how health determinants are modifiable with policy interventions. Our findings can assist the Cambodian government in advancing its universal health coverage goals and offer insights for other countries aiming to extend coverage to similar population groups.